Lower limb arteriopathy in diabetics at the Oueme-Plateau Provincial Hospital in Porto-Novo: Frequency and Associated Factors. - WANVOEGBE, FINANGNON ARMAND; GNINKOUN, COMLAN JULES; HOUEHANOU-SONOU, CORINE; AGBODANDE, KOUESSI ANTHELME (My University, 2023)
Introduction: The distribution of arteriopathy of the lower limbs (ALL) is not familiar in the city of Porto-Novo. The aim of this study was to determine the prevalence and associated factors of ALL in diabetic patients in treatment at the Oueme-Plateau Provincial Teaching Hospital. Methods: This was a crosssectional, descriptive, and analytical study from July 12 to October 10, 2021, at the Oueme-Plateau Provincial Teaching Hospital in Porto-Novo. ALL was screened by performing systolic pressure index (SPI) in all diabetic patients aged at least 18 years, seen in consultation or hospitalization during the study period and who had given their consent. Results: The study registered 165 diabetics and 98.2% of them were type 2. Subjects aged between 55 and 65 years were the most represented (33.9%), with an average age of 59.4 years. Women were in the majority (61.2%), with a sex ratio of 0.6. High blood pressure was associated with diabetes in 61.2% of patients. The prevalence of ALL was 48.5% (80 patients). Obliterative arteriopathy of the lower limbs (OALL) was observed in 70 patients (42.4%), mediacalcosis in 8 patients (4.8%), and mixed arteriopathy in 2 patients (1.2%). In 88.5% of patients, the pathology was symptomless. Factors significantly associated with ALL included advanced age (p = 0.01), the age of the glycemic imbalance (p = 0.03), lack of regular physical activity (p = 0.001) and dyslipidemia (p = 0.008). Conclusion: Pelvic limb arteriopathy is usual among diabetics at Oueme-Plateau Provincial Teaching Hospital. The use of SPI, which enables diagnosis, requires simple, low-cost means, and should be encouraged.
Keywords: ALL; Diabetes; OALL; Porto-Novo; Systolic Pressure Index